Is it Possible to Train Critical Citizens in Colombian Mathematics Classrooms? Possibilities Offered by National Curricular References: ¿Es posible formar ciudadanos críticos en las aulas colombianas de matemáticas? Herramientas que ofrecen los referentes curriculares nacionales (Papeles, 2025)
Introduction: This article aims to present the potential offered by Colombian curricular documents to train critical citizens from the classrooms, in terms of the purposes, contents and methodologies of school mathematics, in accordance with the approaches of Critical Mathematics Education. Methodology: A qualitative methodology with a hermeneutic approach called Content Analysis. Three documents were analyzed: Mathematics Curricular Guidelines (MinEducación, 1998) and Basic Standards of Mathematical Competencies (MinEducación, 2006), as well as the curricular update document entitled Foundations of Basic Learning Rights (MinEducación, 2015). Results and discussion: Among the findings, the recognition of the social dimension of mathematics classes, the importance of the transformation of the curricular organization and the relevance of problema solving in significant contexts as an integrating axis of diverse knowledge for the training of critical citizens are highlighted. Conclusions: Curricular referents recognize that one of the purposes of mathematics education is to develop critical citizens. They emphasize the importance of developing mathematical and technological skills in students, although the development of reflective skills is not explicit and is subject to the epistemological positions of educators regarding their commitment to this training. Finally, they promote different learning environments in meaningful contexts, transforming the roles of students and teachers; fundamental aspects for citizenship training from Critical Mathematics Education.
Keywords: Curriculum; mathematics education; citizenship education; critical literacy